A new climatic chamber for studying soil–atmosphere interaction in physical models - Lozada, Catalina; Caicedo, Bernardo; Thorel, Luc (ICE Publishing, 2019)
A new climatic chamber at the Universidad de Los Andes in Bogotá, Colombia has been designed and built to simulate atmosphere. It has been instrumented to measure various environmental variables, including relative humidity (RH), wind velocity, radiation and temperature. The climatic chamber has been calibrated so that it properly simulates each environmental variable as well as the heat-transfer mechanisms that affect desiccation in soil layers. First, a potential evaporation test was performed in a container filled with water. The weight of the water evaporated was measured, and the interaction with the artificial atmosphere was studied. Then, an actual evaporation test was performed on a soil layer, and the relations among environmental variables and soil properties such as soil temperature, water content and suction were determined. The principal results show the existence of a gradient of RH at the soil–atmosphere interface. Also, a comparison between potential and actual evaporation indicates that suction is the main soil property that affects the actual evaporation rate.

Se ha diseñado y construido una nueva cámara climática en la Universidad de los Andes de Bogotá (Colombia) para simular la atmósfera. Se ha instrumentado para medir diversas variables ambientales, como la humedad relativa (HR), la velocidad del viento, la radiación y la temperatura. La cámara climática ha sido calibrada para que simule adecuadamente cada variable ambiental, así como los mecanismos de transferencia de calor que afectan a la desecación en las capas del suelo. En primer lugar, se realizó una prueba de evaporación potencial en un recipiente lleno de agua. Se midió el peso del agua evaporada y se estudió la interacción con la atmósfera artificial. A continuación, se realizó una prueba de evaporación real en una capa de suelo y se determinaron las relaciones entre las variables ambientales y las propiedades del suelo, como la temperatura, el contenido de agua y la succión. Los principales resultados muestran la existencia de un gradiente de HR en la interfaz suelo-atmósfera. Asimismo, la comparación entre la evaporación potencial y la real indica que la succión es la principal propiedad del suelo que afecta a la tasa de evaporación real.
Keywords: Atmósfera; Atmosphere; Suelos - Absorción y adsorción; Soil absorption and adsorption; Permeabilidad de suelos; Soil permeability; Environment; Models (physical)